O008 Are donor paediatric pancreatic grafts a viable option for pancreas transplantation, even in an adult recipient?. (22nd July 2022) - Tinker, RJ; Owen, RV; Tiwari, N; Wilson, CH; White, SA
Abstract: Introduction: Very few studies have analysed the outcomes of paediatric pancreatic grafts for whole pancreas transplantation. These grafts represent an important resource for both paediatric and adult recipients. Smaller donor grafts may have an increased risk of thrombosis and potentially less chance of insulin independence due to reduced beta cell mass in larger recipients. The aim of this study was to analysis of the use of donor paediatric pancreatic grafts for whole pancreas transplants. Methods: NHSBT registry data from 2003–2021 was obtained (n=2, 998), those with missing data specifically pertaining to paediatric grafts were removed leaving a final cohort of 2, 812. Age groups were categorized by school year (pre-school, infants, junior and high-school students) to best represent paediatric growth and milestones. Univariate survival analysis was performed using Kaplan Meier plots and multi-variate analysis with cox regression models. Results: The majority of grafts utilized were from donors >18 years old (n=2, 402, 85.4%). 12.4% (n=350) were aged between 12–18 years, 1.45% (n=41) 8–11 years, 0.6% (n=17) 4–7 years and our smallest group aged <4 years 0.07% (n=2). We accept numbers are small for the youngest cohorts but there were no statistically significant differences between the different age groups in terms of either graft survival at 1 year (p=0.707) or 3 years (p=0.129) or patient survival at 1 year (p=0.06) or at 3 years (p=0.30). Conclusion: This study has shown comparable graft and patient outcomes after pancreas transplantation irrespective of donor age and may help facilitate improved rates of graft utilization. Take-home message: Paediatric donors have very similar outcomes to adult donors. Here we provided evidence that paediatric transplants for the pancreas should be more widely utilised.